INFLUENCE OF HEADTEACHERS' INVOLVEMENT OF FEMALE TEACHERS ON GIRLS' ACCESS TO PUBLIC PRIMARY EDUCATION IN GARISSA SUB-COUNTY, GARISSA COUNTY, KENYA - Osman, Garat Hassan; Njoroge, Benson; Kenei, Reuben (African Journal of Education and Practice, 2020)
Purpose: The purpose of this study was to assess the influence of headteachers' involvement of female teachers on girls' access to primary education in Garissa Sub-County, Garissa County, Kenya. The study was guided by the Management Practices and Pearson's Gender Relations Theories. Methodology: The study adopted mixed methodology and descriptive survey research design. Data analysis began by identifying common themes. The target population comprised of 28 headteachers, 302 teachers, 873 girls in classes VII & VIII and three (3) Curriculum Support Officers (CSOs) totaling to 1206 from which 300 respondents were determined using Yamane's Formula. Stratified sampling was used to create three strata based on the number of zones in Garissa Sub-County. From each zone, four headteachers and 56 teachers were selected using simple random sampling to avoid bias. The procedures adopted enabled the researcher to sample 12 headteachers, 168 teachers, 117 girls in classes VII & VIII and three (3) CSOs. Qualitative data were analyzed thematically along the objectives and presented in narrative forms. Quantitative data were analyzed using descriptive statistics such as frequencies and percentages and inferentially using Pearson's Product Moment Correlation with the help of Statistical Package for Social Sciences (SPSS Version 23) and presented using tables. Findings: The study established that headteachers' management practices such as involvement of female teachers influence the number of girls who are enrolled into primary schools. Unique Contribution to Theory, Policy and Practice: Thus, the study recommends that the Ministry of Education should recruit and work with female teachers to enhance girls' access to primary education and to inform future policy development.